STUDYING THE EFFECT OF LACTIC ANAEROBIC TRAINING ON SOME PHYSIOLOGICAL AND BIOCHEMICAL RESPONSES OF BOYS DURING ADOLESCENCE - Lecturer. Ali Hussein Ali Al-Saeedi (Ph.D.) (Proximus Journal Publishing, 2025)
This study examines the physiological and biochemical effects of lactic anaerobic endurance training on male adolescents aged 12 to 16. While there is a growing interest in youth athletic training, concerns persist regarding the potential health risks associated with intensive lactic anaerobic training in this age group. The research problem arises from the limited data on how such training affects children's physiological development and overall health, emphasizing the need for evidence-based guidelines for coaches and trainers. The study involved 12 athletes, categorized into two age groups: 12–14 years and 14–16 years. Both groups participated in an eight-week lactic anaerobic endurance training program. Physiological and biochemical parameters—including vital capacity, maximal oxygen consumption (VO₂ max), blood pH levels, lactic acid concentration, creatine kinase (CK), lactate dehydrogenase (LDH), and running performance at 300 and 500 meters—were measured pre- and post-training
Keywords: measured; biochemical; anaerobic endurance